ARES (Augmented Reality-Ethnoscience): development of digital learning media to improve critical thinking ability in elementary school students - Zidni Alfian Barif; Apnorlince Paulus; Raihatul Jannah; Alwiana Hamidah Nugroho; Nabila Ariiqah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The 21st century presents various global challenges that require the development of students’ critical thinking skills; however, the lack of contextual digital media to support ecosystem observation has contributed to low levels of students’ critical thinking ability. This study aims to develop and examine the effectiveness of ARES, an Augmented Reality digital learning media integrated with the ethnoscience of Perelek Runtah, in improving students’ critical thinking skills. The research employed the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate) using validation sheets, critical thinking tests, and questionnaires, with a sample of 24 fifth-grade elementary school students. The media trial was conducted using a quasi-experimental one-group pretest–posttest design across four learning sessions. Expert validation results obtained a score of 88% (very feasible), while the average posttest score (56.0) was higher than the pretest score (29.9). A paired-sample t-test showed a significant difference between pretest and posttest scores (p = 0.000 < 0.05), and the N-Gain value of 0.37 indicated a medium improvement. Student response results showed an average score of 82.91% (Highly Practical). Therefore, it can be concluded that ARES is effective in improving students’ critical thinking skills and is recommended for use in elementary school science learning.